Enhancing the sustainability of geotechnical engineering with utilization of fly Ash - Hasan Majed Alqawasmeh (Discover Materials)
Abstract Massive amounts of fly ash (FA) are dumped carelessly leading to a negative influence on the environment. However, FA contains several advantages when it is used in geotechnical engineering and civil engineering projects which not only dispose of waste but also improve sustainability. In addition to offering a promising solution to the disposal issue, the use of waste materials in civil engineering projects also offers an affordable substitute for conventional materials which preserves natural resources. Many scholars' studies show how FA is used and how it affects the geotechnical characteristics of the soil. Despite extensive research, the assessment of FA's suitability is complicated due to the chemical composition of FA which varies significantly between sources. This variability can affect how FA interacts with different soil types, leading to inconsistent results in terms of soil improvement and geotechnical properties. Therefore, a comprehensive review is required that compiles all effective data and gives the user simple instructions about using FA. This article reviews the current state of the art research on the physical properties of FA, chemical composition of different countries FA, Atterberg limit, compaction properties, California bearing ratio, unconfined compressive strength, shear strength compression, and swelling index. Results showed that adding FA to soil increased its geotechnical qualities, but the effect depends on the type of soil and specific conditions, such as moisture content, compaction, and the percentage of FA added. The higher percentages of FA led to a decline in geotechnical characteristics. The assessment, therefore, advises that FA may be added up to optimum percentages which generally 20% depending on its source and chemical composition.